On the Hyers-Ulam Stability of the First-Order Difference Equation. (4th August 2016) - Jung, Soon-Mo; Nam, Young Woo
Abstract : We prove Hyers-Ulam stability of the first-order difference equation of the form x i + 1 = F ( i, x i ), where F is a given function with some moderate features. Moreover, we introduce some conditions for the function F under which the difference equation is not stable in the sense of Hyers and Ulam.